Record Charge Carrier Diffusion Length in Colloidal Quantum Dot Solids via Mutual Dot-To-Dot Surface Passivation - Carey, Graham H (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.